2017
DOI: 10.1093/hmg/ddx120
|View full text |Cite
|
Sign up to set email alerts
|

Glucocerebrosidase deficiency in dopaminergic neurons induces microglial activation without neurodegeneration

Abstract: Mutations in the GBA1 gene encoding the lysosomal enzyme glucocerebrosidase (GBA1) are important risk factors for Parkinson's disease (PD). In vitro, altered GBA1 activity promotes alpha-synuclein accumulation whereas elevated levels of alpha-synuclein compromise GBA1 function, thus supporting a pathogenic mechanism in PD. However, the mechanisms by which GBA1 deficiency is linked to increased risk of PD remain elusive, partially because of lack of aged models of GBA1 deficiency. As knocking-out GBA1 in the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 53 publications
1
26
0
Order By: Relevance
“…Since gba haploinsufficency did not result in significantly enhanced SNCA levels or abundance of SNCA pathology in terminal mice, another, yet unknown secondary function of GCase protein in distinct neuronal populations may initiate or contribute to the earlier and more severe symptoms in gba +/− // SNCA A53T mice. This is supported by a study of dopaminergic neurons from aged mice with a conditional GBA1 knock-out, which had no motor dysfunction and no midbrain accumulation of endogenous SNCA [40]. It has been proposed that deficient GCase promotes cellular cascades contributing to earlier Parkinson pathogenesis and synaptic dysfunction [16].…”
Section: Discussionmentioning
confidence: 97%
“…Since gba haploinsufficency did not result in significantly enhanced SNCA levels or abundance of SNCA pathology in terminal mice, another, yet unknown secondary function of GCase protein in distinct neuronal populations may initiate or contribute to the earlier and more severe symptoms in gba +/− // SNCA A53T mice. This is supported by a study of dopaminergic neurons from aged mice with a conditional GBA1 knock-out, which had no motor dysfunction and no midbrain accumulation of endogenous SNCA [40]. It has been proposed that deficient GCase promotes cellular cascades contributing to earlier Parkinson pathogenesis and synaptic dysfunction [16].…”
Section: Discussionmentioning
confidence: 97%
“…A susceptibility of DA neuronal development to the deleterious effects of GBA1 mutations has been reported in some in vivo models of GBA1 deficiency but not in others. Zebrafish with a truncation in the ortholog of human GBA1 display a decrease in motor activity and a reduction in DA neuronal cell count, and this effect is independent from α-synuclein neurotoxicity, as zebrafish lack this gene ( Keatinge et al., 2015 ); similarly, mutations or deletion of GBA1 Drosophila orthologs cause dopaminergic neuronal loss, defective locomotion, and a shorter life span ( Maor et al., 2016 , Sanchez-Martinez et al., 2016 ); however, in a GBA −/− medaka model of neuronopathic GD, the mutant fish exhibited brain infiltration of Gaucher-like cells, microgliosis, and progressive neuronal loss that included but was not limited to TH-positive cells ( Uemura et al., 2015 ); and in mice with a targeted deletion of GBA1 in mature, DAT-expressing midbrain dopaminergic neurons (DAT- GBA1 -KO mice) there was no reduction in the number of TH-positive neurons in the substantia nigra of the mutant mice ( Soria et al., 2017 ). Thus, the effect of GBA1 mutation on DA neuronal numbers and survival seems to be model dependent, and our results using GD iPSC model will need to be validated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…These results were confirmed by the studies from Rocha et al (2015b) and Mus et al (2019), both showing that a CBE-induced drop in GCase enzymatic activity activates microglia throughout the brain. Interestingly, using a DAT-GBA1-KO mouse displaying selective homozygous GBA1 disruption in midbrain dopamine neurons, Soria et al (2017) demonstrated strong microglial activation in the substantia nigra of these mice, without any evidence of dopaminergic cell loss, alpha-synuclein accumulation, or motor abnormalities.…”
Section: Glucocerebrosidase and Neuroinflammationmentioning
confidence: 99%
“…GCase defects may also contribute to neuroinflammation, a phenomenon that is increasingly implicated in PD pathogenesis, as suggested by various studies demonstrating that a reduction in GCase activity is associated with clear activation of microglia in the brain parenchyma (Ginns et al, 2014;Rocha et al, 2015c;Soria et al, 2017;Mus et al, 2019).…”
Section: Introductionmentioning
confidence: 99%